Modeling of Equilibrium Water Condensation in Natural Gas Flowing Through Joule Thompson Valve - Karar Balla, Ola Babiker (IRC, 2016)
Natural gas is a hydrocarbon gas mixture that consists mainly of methane and other higher alkanes. However, it may contain some impurities such as carbon dioxide, water, nitrogen, and hydrogen sulphide. The presence of these impurities might cause problems in the pipeline, fittings, valves and the control system due to the formation of hydrates that will block the flow line. The gas hydrates trapped within the water droplets has to be removed before further processing of the natural gas. Dehydration methods used in the industry are absorption, adsorption, refrigeration and membrane. However, there are some drawbacks associated with these methods. Dehydration of natural gas can be achieved through Joule Thompson effect where the gas expands freely after flowing through a throttle or choke valve and condensation occurs due to the temperature drop. Current project developed a model to describe the condensation phenomenon in natural gas. The model is validated through comparing the results obtained from the simulation with the experimental values. Lastly, a sensitivity analysis were performed to increase the water removal efficiency through changing the inlet pressure, throttle diameter and the natural gas composition.